The role of proangiogenic cytokines in predicting sepsis in febrile neutropenic children with cancer - Çakmakcı, Selma; Sarı, Neriman; Sönmez, Çiğdem; Ergürhan İlhan, İnci (The Turkish Journal of Pediatrics, 2024)
Background. We assessed the relationship between sepsis occurrence and the serum levels of angiopoietin (Ang-1, Ang-2), vascular endothelial growth factor (VEGF) and soluble fms-like tyrosine kinase-1 (sFlt-1) in pediatric patients with cancer-related febrile neutropenia.Methods. Fifty-two children with malignant tumors who experienced 86 episodes of febrile neutropenia (FN) were examined between June 2016 and June 2018. Each FN episode was considered a separate event and the total number of FNs were recorded (86 FN episodes = FN group). The control group consisted of 21 healthy children. Ang-1, Ang-2, VEGF-A and sFlt-1 were measured at the baseline and 48th hour of each FN episode –alongside routine characterization of inflammation (C-reactive protein; white blood cell and absolute neutrophil count).Results. Among the episodes, 29 (34.5%) developed sepsis while 57 were classified as non-complicated FN. The baseline values of patients and controls were significantly different for Ang-1, Ang-2, VEGF and sFlt-1 values (all, p < 0.05). In the subgroup with sepsis, Ang-2 values were higher than in the subgroup without sepsis (p = 0.017). In predicting sepsis, Ang-2 had 60.7% sensitivity and 66.7% specificity at the 74.6 cut-off value (AUC: 0.662 [95%CI: 0.541 – 0.783], p = 0.022), Ang-2 / Ang-1 ratio had 65.5% sensitivity and 60.0% specificity at the 0.405 cut-off value (AUC: 0.633 [95%CI: 0.513 – 0.753], p = 0.046).Conclusions. Our results reveal that Ang-2 and Ang-2/Ang-1 were higher in the sepsis group and Ang-2 might be a biomarker to indicate the risk of sepsis in patients with FN and/or cancer.
Keywords: sepsis; children; febrile neutropenia; angiopoietin; vascular endothelial growth factor; soluble fms-like tyrosine kinase